Emollient bath additives for the treatment of childhood eczema (BATHE): multi-centre pragmatic parallel group randomised controlled trial of clinical and cost-effectiveness - Santer, Miriam; Ridd, Matthew J.; Francis, Nick A.; Stuart, Beth; Rumsby, Kate; Chorozoglou, Maria; Becque, Taeko; Roberts, Amanda; Liddiard, Lyn; Nollett, Claire; Hooper, Julie; Prude, Martina; et al. (BMJ Publishing Group, 2018)
Objectives: To determine the clinical and cost-effectiveness of including emollient bath additives in the management of childhood eczema. Trial design: Pragmatic randomised open-label superiority trial with two parallel groups. Setting and recruitment: 96 general practices in Wales, West of England and Southern England. Invitation by personal letter or opportunistically by usual clinical team. Participants: Children were eligible to participate if aged over 12 months and less than 12 years, fulfilling UK Diagnostic Criteria for Atopic Dermatitis. Children with inactive or very mild eczema (5 or less on Nottingham Eczema Severity Scale) were excluded, as were children who bathed less than once a week, or whose carers were not willing to accept randomisation. 483 were randomised and one withdrew, leaving 482 children in the trial: 51% female, 84% white, mean age 5 years. Interventions: The intervention group were prescribed emollient bath additives by their usual clinical team and were asked to use them regularly for 12 months. The control group were asked to use no bath additives for 12 months. Both groups continued with standard eczema management and were given standardised advice on how to wash. Primary outcome: Eczema control measured by Patient Oriented Eczema Measure (POEM, range 0-28) weekly for 16 weeks. Secondary outcomes: Eczema severity over 1 year (4-weekly POEM from baseline to 52 weeks); number of eczema exacerbations resulting in primary healthcare consultation; disease-specific quality of life (QOL) (Dermatitis Family Impact); generic QoL (Child Health Utility-9D); resource utilisation; type and quantity of topical corticosteroid/calcineurin inhibitors prescribed. Randomisation: 483 children were randomised (1:1) using online software, stratified by recruiting centre. Results: 95.6% (461/482) of participants completed at least one post-baseline POEM, so were included in the analysis, and 76.8% (370/482) of participants completed questionnaires for more than 80% of the time points for the primary outcome (12/16 weekly questionnaires to 16 weeks). The mean Baseline POEM was 9.5 (s.d. 5.7) in the bath additives group and 10.1 (s.d. 5.8) in the no bath additives group. The mean POEM over the 16-week period was 7.5 (s.d. 6.0) in the bath additives group and 8.4 (6.0) in the no bath additives group. There was no statistically significant difference in weekly POEM scores between groups over 16 weeks. After controlling for baseline severity and confounders (ethnicity, topical corticosteroid use, soap substitute use) and allowing for clustering of participants within centres and responses within participants over time, POEM scores in the no bath additive group were 0.41 points higher than in the bath additive group (95% CI -0.27 to 1.10), below the published minimal clinically important difference for POEM of 3 points. There was no difference between groups in secondary outcomes, economic outcomes or in adverse effects. Conclusions: This trial found no evidence of clinical benefit from including emollient bath additives in the standard management of childhood eczema. Further research is needed into optimal regimens for leave-on emollient and use of soap substitutes for children with eczema.